Changing learning conversations : an action research model of reflective professional development : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Education, Massey University, Albany, New Zealand - Harnett, Jennifer Anne (Massey University, 2007)
A growing body of international research has indicated that teacher effectiveness is the most important factor affecting student achievement. At the heart of effective teaching and learning are learning conversations, in which teachers play a pivotal role in mediating learning by orchestrating discussion with students. This action research study had a dual purpose, firstly to investigate the effects of teachers’ knowledge and thinking on their ability to mediate students’ learning in classroom learning conversations, and secondly to provide the participating teachers with opportunities to investigate and develop their professional knowledge and practice. The action research approach allowed the collection of substantive information about teachers’ thinking and practice, while at the same informing and developing that practice through cycles of data collection, analysis, and reflection. The study involved two New Zealand primary school teachers in four cycles of action research. Information was gathered about the teachers’ knowledge, thinking, and practice through semi-structured interviews, classroom observations, and reflective journals. Observation transcripts were analysed, coded, discussed, and reflected upon during reflection days at the end of each cycle. The initial findings of the study revealed that although the two teachers were very different in their teaching styles, there were strong similarities in the fragmented nature of their knowledge of learning and assessment theory. Discrepancies were found between the teachers’ espoused theories and their theories-in-use. In addition, the teachers’ practice was strongly influenced by implicit beliefs and routinised behaviours, which had a powerful and often detrimental effect on the quality of their interactions with students. However, the process of examining the evidence in their own lesson transcripts enabled the teachers to develop awareness of weaknesses in their practice. This was a catalyst for reflection that resulted in change and improvement. After an initial regression both teachers made small but incremental changes in their interactions with students. By the end of the final cycle both teachers had appreciably improved the quality of their classroom learning conversations. The study demonstrates the effectiveness of classroom-based action research as a model for reflective professional development.
Keywords: Effective teaching; Interaction analysis; Action research; Fields of Research::330000 Education::330300 Professional Development of Teachers